Comprehension, retention and self-efficacy in biology within the framework of CAI-enriched learning model - Openia, Bryan C. (Iloilo City University of the Philippines Visayas, 2016)
This quanti-qualitative study aimed to determine effectiveness of the computer-aided instructional (CAI) material and an inquiry-based learning model on the learning of the learners. The study examined the comprehension, retention and self-efficacy of learners when grouped according to sex and length of computer use in learning biology as well as variables that correlated with gain in comprehension and retention. It also determined the learning experience of the learners. The learners were pretested and posttested prior to the study. Wilcoxon Signed rank test showed significant difference between gain in comprehension (male and female, p+.000 ; infrequent, p=.007 ; moderate, p=.003,, frequent, p=.000), between pretest and posttest of self-efficacy (male and female, p=.000 ; infrequent, p=.008 ; moderate, p=.003, frequent, p=.000) and, between posttest-comprehension and etention (male,p=.010 ; female, p=.017 ; infrequent, p=.000 ; moderate, p=.005, frequent,p=.007) of learners when grouped according to sex and length of computer use. This revealed that students increased in comprehension and self-efficacy and retained knowledge when grouped according to sex and length of computer use. Result of the Mann-Whitney U test showed no significant differences on the gain in comprehension (p=.341), retention (p=.298) and self-efficacy (p=.153) between male and female. When grouped according to length of computer use, Kruskall Wallis H test showed significant differences on the gain in comprehension (p=.000), retention (p=.000) and self-efficacy (p=.000) among the different types of users. Result of the Spearman's rho correlatio r showed that posttested-comprehension is very significantly correlated with the comprehension (p=.000) of the learners. None of the variables (pretest comprehension, p=.867 ; pretest self-efficacy, p=465 ; posttest self-efficacy, p=.700) were found to be significantly correlated with retention.The results of the study provide insights for teachers and administrators to review approaches and educational tools in teaching, and to consider the possibility of incorporating CAI with an inquiry-based learning approach in a biology learning environment.
Special Problem (M. Ed-Biology)--Iloilo City : University of the Philippines Visayas, August 2016.